RECORD-2: phase II randomized study of everolimus and bevacizumab versus interferon α-2a and bevacizumab as first-line therapy in patients with metastatic renal cell carcinoma - Ravaud, A; Barrios, C H; Alekseev, B; Tay, M-H; Agarwala, S S; Yalcin, S; Lin, C-C; Roman, L; Shkolnik, M; Anak, O; Gogov, S; Pelov, D; et al. (Annals of oncology, 2015)
BACKGROUND: The open-label, phase II RECORD-2 trial compared efficacy and safety of first-line everolimus plus bevacizumab (EVE/BEV) with interferon plus bevacizumab (IFN/BEV) in patients with metastatic renal cell carcinoma. PATIENTS AND METHODS: Previously untreated patients were randomized 1:1 to bevacizumab 10 mg/kg every 2 weeks with either everolimus 10 mg/day (EVE/BEV) or interferon (9 MIU 3 times/week, if tolerated) (IFN/BEV). Tumor assessments occurred every 12 weeks. The primary objective was the assessment of treatment effect on progression-free survival (PFS), based on an estimate of the chance of a subsequent phase III trial success (50% threshold for phase II success). RESULTS: Baseline characteristics were balanced between the EVE/BEV (n = 182) and IFN/BEV (n = 183) arms. The median PFS was 9.3 and 10.0 months in the EVE/BEV and IFN/BEV arms, respectively (P = 0.485). The predicted probability of phase III success was 5.05% (hazard ratio = 0.91; 95% confidence interval 0.69-1.19). The median duration of exposure was 8.5 and 8.3 months for EVE/BEV and IFN/BEV, respectively. The percentage of patients discontinuing because of adverse events (AEs) was 23.4% for EVE/BEV and 26.9% for IFN/BEV. Common grade 3/4 AEs included proteinuria (24.4%), stomatitis (10.6%), and anemia (10.6%) for EVE/BEV and fatigue (17.1%), asthenia (14.4%), and proteinuria (10.5%) for IFN/BEV. The median overall survival was 27.1 months in both arms. CONCLUSIONS: The efficacy of EVE/BEV and IFN/BEV appears similar. No new or unexpected safety findings were identified and, with the exception of proteinuria in about one-fourth of the population, EVE/BEV was generally well tolerated. CLINICAL TRIAL REGISTRY AND TRIAL REGISTRATION NUMBER: ClinicalTrials.gov: NCT00719264.
Keywords: nádory ledvin; metastatic renal cell carcinoma; papilární karcinom; Humans; Interferon-alpha; lidé středního věku; Female; Aged; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; combination targeted therapy; senioři; lidé; Adult; Neoplasm Metastasis; metastázy nádorů; bevacizumab; ženské pohlaví; staging nádorů; Carcinoma, Papillary; Follow-Up Studies; Male; Middle Aged; prognóza; Antineoplastic Combined Chemotherapy Protocols; first-line; everolimus; Aged, 80 and over; karcinom z renálních buněk; interferon alfa; Bevacizumab; Young Adult; senioři nad 80 let; Carcinoma, Renal Cell; Neoplasm Staging; míra přežití; mužské pohlaví; Everolimus; Kidney Neoplasms; Prognosis; následné studie; Survival Rate